Genomic signature to guide adjuvant chemotherapy treatment decisions for early breast cancer patients in France: a cost-effectiveness analysis - Curtit, Elsa; Bellanger, Martine Marie; Nerich, Virginie; Hequet, Delphine; Frenel, Jean-Sebastien; Cristeau, Olivier; Rouzier, Roman (Frontiers in Oncology, 2023)
Chemotherapy (CT) is commonly used as adjuvant treatment for women with early breast cancer (BC). However, not all patients benefit from CT, while all are exposed to its short- andlong-term toxicity. The Oncotype DX® test assesses cancer-related gene expression to estimate the risk of BC recurrence and predict the benefit of chemotherapy. The aim of this study was to estimate, from the French National Health Insurance (NHI) perspective, the cost-effectiveness of the Oncotype DX® test compared to standard of care (SoC, involving clinicopathological risk assessment only) among women with early, hormone receptor-positive, human epidermal growth factor receptor 2-negative BC considered at high clinicopathological risk of recurrence. Clinical outcomes and costs were estimated over a lifetime horizon based on a two-component model that comprised a short-term decision tree representing the adjuvant treatment choice guided by the therapeutic decision support strategy (Oncotype DX® test or SoC), and a Markov model to capture long-term outcomes. In the base case, the Oncotype DX® test reduced CT use by 55.2% and resulted in 0.337 incremental quality-adjusted life-years gained and cost savings of €3,412 per patient, compared with SoC. Being more effective and less costly than SoC, Oncotype DX® testing was the dominant strategy. Widespread implementation of Oncotype DX® testing would improve patient care, provide equitable access to more personalized medicine, and bring cost savings to the health system.